2017
DOI: 10.1021/acsami.6b14863
|View full text |Cite
|
Sign up to set email alerts
|

Differential Adhesive and Bioactive Properties of the Polymeric Surface Coated with Graphene Oxide Thin Film

Abstract: Surface engineering of implantable devices involving polymeric biomaterials has become an essential aspect for medical implants. A surface enhancement technique can provide an array of unique surface properties that improve its biocompatibility and functionality as an implant. Polyurethane-based implants that have found extensively acclaimed usage as an implant in biomedical applications, especially in the area of cardiovascular devices, still lack any mechanism to ward off bacterial or platelet adhesion. To b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…Flat coatings without sharp edges, identical to the coatings containing GNP-M5ox obtained here were also reported by others using GO [20]. Thampi et al also observed wrinkled topography when spraying GO onto electrospun polycarbonate urethane (PCU) membranes [74]. Overall, coatings with GNP:PU ratio of 1:0.5, and specially with GNP concentration of 0.5 mg/mL, seemed to present more uniform and thus more promising surfaces.…”
Section: Pu/gnp Coatingssupporting
confidence: 88%
“…Flat coatings without sharp edges, identical to the coatings containing GNP-M5ox obtained here were also reported by others using GO [20]. Thampi et al also observed wrinkled topography when spraying GO onto electrospun polycarbonate urethane (PCU) membranes [74]. Overall, coatings with GNP:PU ratio of 1:0.5, and specially with GNP concentration of 0.5 mg/mL, seemed to present more uniform and thus more promising surfaces.…”
Section: Pu/gnp Coatingssupporting
confidence: 88%
“…Also, the short half-lives of such proteins in physiological conditions have led to some scepticism about the feasibility of using them as a therapeutic agent. In the recent years, there is a growing interest in using graphene-based materials for tissue engineering and other biomedical applications [ 20 , 21 ]. Graphene and reduced graphene oxide (rGO) are good conductors of electricity and have thus been used for neural tissue engineering applications [ 20 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thampi et al and Cortella et al used surface functionalization with antithrombotic agents or immobilization of molecules, such as polyethylene oxide (PEO), heparin, albumin, and chitosan (CS), to improve the blood compatibility of biomedical devices [ 2 , 43 ]. Roth et al and Yu et al recommended the application of biologically active substances, such as anticoagulants [ 14 ], fibrinolytic enzymes or proteins [ 14 ], heparin [ 22 ], CS [ 22 ], and dextran sulfate (DS) [ 22 ], as surface modification substances [ 14 , 22 ] in order to enhance the compatibility of PUs with the blood components.…”
Section: Discussionmentioning
confidence: 99%